1977
DOI: 10.1111/j.1440-1681.1977.tb02615.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Fructose, Dextrose and Ethanol on Human Performance

Abstract: 1. The effects of orally administered fructose (1.2 g.kg-1) and dextrose (1.2 g.kg-1) on the performance decrement induced by ethanol (1.0 g.kg-1) in a series of perceptual, cognitive and motor tests were studied in twelve healthy, paid University student volunteers using a double-blind cross-over design. Ethanol was consumed at a constant rate over 20 min and the hexoses or placebo were given approximately 40 min later. 2. The peak blood ethanol concentration was attained earlier when the subjects also receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, our finding that a sugar can attenuate alcohol intoxication without affecting BAL is new. Thus,previous studies finding attenuation effects have also found BAL differences, possibly due to the use of fructose (Franks et al 1977;Goldberg et al t979a;Perl and Starmer 1983). They attribute their results to absorption effects, but metabolism changes induced by fructose may have been involved (Mezey 1981;Crownover et al 1986).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, our finding that a sugar can attenuate alcohol intoxication without affecting BAL is new. Thus,previous studies finding attenuation effects have also found BAL differences, possibly due to the use of fructose (Franks et al 1977;Goldberg et al t979a;Perl and Starmer 1983). They attribute their results to absorption effects, but metabolism changes induced by fructose may have been involved (Mezey 1981;Crownover et al 1986).…”
Section: Discussionmentioning
confidence: 83%
“…This has been shown in both rats (Mueller et al 1971 ;Jones et al 1979) and in humans (Franks et al 1977;Goldberg et al 1979a, b;Perl and Starmer 1983). These findings have been seen with fructose or with syrups that combine fructose with other sugars.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Three of the most sedative compounds with potent H I antihistaminic properties, chlorpheniramine, diphenhydramine and amitriptyline, all consistently increased body sway. Drugs with anticonvulsant properties (phenytoin, amylobarbitone, meproba- Franks et al, 1976Franks et al, 1977Seppala et al, 1982Starmer and Bird, 1984Linnoila et al, 1984Hill et al, 1982 Linnoila et ol., 1984Scott et al, 1982Franks et al, 1975Franks et al, 1976Crawford et al, 1976Franks et al, 1981Bond and Lader, 1986Franks et al, 1978Franks et al, 1976Franks et al, 1979Belgrave et al, 1979aBelgrave et al, 1979bLinnoila et al, 1984Scott et al, 1982Bond and Lader, 1986Scott et al, 1982 Seppala et al, 1982Castleden et al, 1987Castleden et al, 1987Mattila et al, 1984McClelland 1987bNicholson et al, 1988Nikaido and Ellinwood, 1987Nikaido and Ellinwood, 1987Briggs et al, 1980Swift et al, 1987aMattila et al, 1984Nikaido and Ellinwood, 1987Nikaido and Ellinwood, 1987Hill et al, 1982 mate, tetrahydrocannabinol) also increased sway. Psychostimulants/ cerebral activating drugs (dexamphetamine, caffeine, Hydergine and denbufylline) all showed no significant effect on sway.…”
Section: Resultsmentioning
confidence: 99%